Effect of pulmonary rehabilitation on dyspnea and exercise tolerance in patients with interstitial lung disease: a systematic review. (15th August 2022) - DePietro, Nicholas; Rinaldi, Jennifer; Nieschwitz, Courtney; Robinson, Heather; Walter, Alysha
Abstract: Purpose: Pulmonary rehabilitation (PR) and exercise training have proven effective for dyspnea and exercise tolerance for individuals with chronic obstructive pulmonary disease (COPD) but little is known of its effect on interstitial lung disease (ILD). There is a need in the literature to systematically review the effect of these interventions on individuals with ILD concerning exercise tolerance and/or dyspnea. Methods: This systematic review utilized PRISMA guidelines to conduct the reporting of the findings and was registered with PROSPERO (CRD42020186513). Databases searched included: PubMed, CINAHL, ProQuest, Scopus, and Web of Science. Independent screening was performed by two authors with a third acting as a tiebreaker when consensus was not reached. Randomized control trials (RCTs) were included with subjects over 18 years old with a diagnosis of ILD who complete either pulmonary rehabilitation (PR) or exercise training interventions and included the six minutes walk test (6MWT) to measure exercise tolerance and/or outcomes to measure dyspnea. Studies were also included if they were published between 2008 through the date of study collection. A quality assessment was then performed on each RCT using the PEDro score with those with a rating of six or greater being included. Results: Eight studies meeting inclusion criteria were included in this review with statistical significance reported in seven of the studies for short-term improvements and in two of the studies for long-term improvements in exercise tolerance. Six reported statistical significance for short-term improvements in dyspnea and two studies reported statistical significance for long-term improvements of dyspnea. Conclusion: Individuals with ILD demonstrate improvements in exercise tolerance and symptoms of dyspnea after participating in PR or exercise training interventions.